Depression and non-suicidal self-injury: the mediating roles of childhood trauma and impulsivity - Su, Wenjing; Liu, Hao; Zhou, Xiaoyan; Huang, Xueping (Frontiers in Psychiatry, 2025)
BackgroundThis study investigates the factors contributing to non-suicidal self-injury (NSSI) in individuals with depressive disorders, with a focus on how childhood trauma and impulsivity may function as mediating mechanisms. The findings aim to establish a theoretical framework that enhances clinicians’ ability to assess suicide-related risks in this population more accurately and promptly.MethodsThis cross-sectional study enrolled patients diagnosed with depression who were hospitalized at Chongqing Mental Health Center between June 2019 and November 2021. All participants completed self- report questionnaires assessing demographic characteristics, NSSI behaviors, depression, anxiety, childhood trauma, impulsivity, family environment, parenting, and experiences in close relationships. Participants were divided into two groups based on NSSI behavior: the NSSI group and the non-NSSI group.ResultsA total of 265 patients were included, 26.79% of whom were male. The NSSI group consisted of 150 patients (mean age = 17.50 ± 3.88 years), while the non-NSSI group included 115 patients (mean age = 23.06 ± 6.92 years). Binary logistic regression analysis identified several factors significantly associated with NSSI in patients with depression: gender (OR = 2.254, 95% CI: 1.083–4.693, P = 0.03), age (OR = 0.776, 95% CI: 0.708–0.851, P < 0.001), number of hospitalizations (OR = 1.747, 95% CI: 1.128–2.705, P = 0.012), suicide attempts (OR = 14.131, 95% CI: 4.023–49.64, P < 0.001), relationship duration (OR = 1.031, 95% CI: 1.009–1.045, P = 0.005), anxiety (OR = 1.03, 95% CI: 1.006–1.054, P = 0.015), sexual abuse (OR = 1.158, 95% CI: 1.036–1.294, P = 0.01), and negative thoughts (OR = 3.108, 95% CI: 1.101–8.774, P = 0.032). In addition, childhood trauma and impulsivity were found to partially mediate the relationship between depressive symptoms and NSSI, accounting for a total indirect effect of 20.52%.ConclusionsThis study identifies multiple factors contributing to NSSI among individuals with depression. Notably, childhood trauma and impulsivity partially mediate the relationship between depressive symptoms and NSSI. These findings offer valuable insights for developing targeted prevention and intervention strategies to address NSSI in this population.